2011
DOI: 10.4049/jimmunol.1100647
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Characterization of Circulating and Functional Antigens Derived from Piperacillin in Patients with Cystic Fibrosis

Abstract: A mechanistic understanding of the relationship between the chemistry of drug antigen formation and immune function is lacking. Thus, mass spectrometric methods were employed to detect and fully characterize circulating antigens derived from piperacillin in patients undergoing therapy and the nature of the drug derived-epitopes on protein which can function as an antigen to stimulate T-cells. Albumin modification with piperacillin in vitro resulted in the formation of two distinct haptens, one formed directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
143
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 100 publications
(152 citation statements)
references
References 47 publications
7
143
0
2
Order By: Relevance
“…Using mass spectrometric methods, we recently identified albumin as a major circulating protein modified with b-lactam antibiotics including flucloxacillin, defined the profile of drug protein conjugation at specific lysine residues with respect to dose and incubation time, and characterized for the first time the sites of modification associated with the stimulation of a clinically relevant drug-specific T-cell response. 13,14,16 Herein, we show that (1) the stimulation of clones with flucloxacillin-pulsed antigen-presenting cells, and (2) the detection of flucloxacillin haptens on albumin in culture are time-dependent. Furthermore, simultaneous measurement of antigenicity and immune responsiveness revealed that the cumulative level of flucloxacillin protein binding at each timepoint studied correlated directly with the strength of the T-cell proliferative response.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Using mass spectrometric methods, we recently identified albumin as a major circulating protein modified with b-lactam antibiotics including flucloxacillin, defined the profile of drug protein conjugation at specific lysine residues with respect to dose and incubation time, and characterized for the first time the sites of modification associated with the stimulation of a clinically relevant drug-specific T-cell response. 13,14,16 Herein, we show that (1) the stimulation of clones with flucloxacillin-pulsed antigen-presenting cells, and (2) the detection of flucloxacillin haptens on albumin in culture are time-dependent. Furthermore, simultaneous measurement of antigenicity and immune responsiveness revealed that the cumulative level of flucloxacillin protein binding at each timepoint studied correlated directly with the strength of the T-cell proliferative response.…”
Section: Discussionmentioning
confidence: 82%
“…Proliferation of patient PBMC (0.15 Â 10 6 /well) against flucloxacillin (0.1-2 mM) and tetanus toxoid (5 lg/mL) was measured using the lymphocyte transformation test. 13 interferon-gamma (IFN-c) and granzyme B-secreting PBMCs were visualized using ELISpot (MabTech, Nacka Strand, Sweden) by culturing PBMC (0.5 Â 10 6 /well; 200 lL) with flucloxacillin (1-2 mM) or PHA (5 lg/mL) for 48 hours. Generation of T-Cell Clones from Patients With Flucloxacillin-Induced Liver Injury.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[41][42][43] Using advanced technologies, such as mass spectrometry, it is possible to define the chemistry of drug-protein conjugation in patients and the nature of the drug-derived epitopes, which can function as an antigen to stimulate T cells. [44][45][46][47][48] There is another mechanism underlying drug-specific T-cell activation. This concept, referred to as the "pharmacological interaction of drugs with immune receptors (p-i concept), " states that drugs by themselves act as antigens interacting in a reversible fashion with immunological receptors.…”
Section: Drug Antigenicitymentioning
confidence: 99%